2018
DOI: 10.1080/23761407.2018.1456995
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the pathological dissociation measures among Chinese – a pilot study using online methods

Abstract: The initial findings suggest that PD can be assessed online in Hong Kong. Further investigation is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…Waller and Ross ( 1997 ) suggested that scores above 35 on the DES-T indicate strong evidence of pathological dissociation. The Chinese version of the DES-T had excellent internal consistency (Cronbach’s alpha = .894) and good construct validity (r = .626 to .653); to detect clinically diagnosed DDs, a cutoff score of 28 had a sensitivity of 93.8% and a specificity of 77.8%, and a cutoff score of 36 had a sensitivity of 81.3% and specificity of 92.6% (Fung, Choi, et al, 2018 ). The mean DES-T score was 14.8 (SD = 15.5) in a Chinese college student sample (Fung, Ho, et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Waller and Ross ( 1997 ) suggested that scores above 35 on the DES-T indicate strong evidence of pathological dissociation. The Chinese version of the DES-T had excellent internal consistency (Cronbach’s alpha = .894) and good construct validity (r = .626 to .653); to detect clinically diagnosed DDs, a cutoff score of 28 had a sensitivity of 93.8% and a specificity of 77.8%, and a cutoff score of 36 had a sensitivity of 81.3% and specificity of 92.6% (Fung, Choi, et al, 2018 ). The mean DES-T score was 14.8 (SD = 15.5) in a Chinese college student sample (Fung, Ho, et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Chinese version of the DDIS has been used in several studies (Chiu et al, 2017 ; Fung, 2016 ). There is a self-report version of the DDIS (SR-DDIS); the Chinese version of the SR-DDIS had a sensitivity of 100% and a specificity of 96.3% in detecting DDs when a cutoff score of 5 was used in the DID Features Section; using the SR-DDIS to diagnose DDs according to DSM-5 rules also had excellent agreement (Cohen’s kappa = .90) with clinical diagnosis (Fung, Choi, et al, 2018 ). In addition, the Borderline Personality Disorder (BPD) Section of the SR-DDIS can diagnose BPD according to DSM-5 rules with a sensitivity of 95.2% and a specificity of 64.9% (Fung et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The DES-T is an 8-item subscale of the original DES and can be used to assess pathological dissociation (Bernstein & Putnam, 1986;Waller et al, 1996;Waller & Ross, 1997). The Chinese version of the DES-T is reliable and valid (Fung, Choi et al, 2018) and has been used in previous studies Fung, Ho et al, 2018). The DES-T is calculated by dividing the sum of the item scores divided by the number of items.…”
Section: Methodsmentioning
confidence: 99%
“…The SR-DDIS is reliable and valid (Ross & Browning, 2017). The Chinese version of the SR-DDIS has been validated and can discriminate participants with and without a DD (Fung, Choi et al, 2018). Moreover, the validity of the BPD section of the DDIS (i.e., SR-DDIS-BPD) has been examined -it can detect DSM-5 BPD with excellent discriminative validity (Fung, Chan, Lee et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…As part of a research project (see Fung, Choi, Chan, & Ross, 2018) approved by the Hong Kong Polytechnic University (PolyU) Research Committee, we used online channels (e.g., Facebook, Blogger, mental health groups and forums) to recruit Hong Kong adults who had a clinical diagnosis of depression to complete an online survey. Online methods are promising and cost-effective for health research purposes and can facilitate recruitment and data collection process (Chan, 2013;Chan & Holosko, 2016.…”
Section: Participantsmentioning
confidence: 99%